The ecological impacts of the climate changes and human colonization on cladocera and chironomid assemblages in oceanic islands – the Holocene Caveiro Lake record (Azores archipelago) - Raposeiro, P. M.; Vilaverde, Joao; Gonçalves, V.; Hernández, Armand; Costa, A. C.; Bao, Roberto; Giralt, Santiago; Sáez, Alberto (2017)
The Azores constitutes the most remote archipelago of the North Atlantic Ocean. Both human colonization and natural changes (mainly climate and active volcanism) have significantly modified its ecosystems. Cladocera and chironomid assemblages in a 805-cm long sediment core from center and deeper (4 m depth) part of Caveiro Lake in Pico Island was studied to assess the impact of environmental and climate changes over the last 5700 yr. Concordant patterns in composition between two biological groups were found, indicating major past environmental changes such as climate fluctuations (arid vs humid periods), volcanic activity, and anthropogenic intervention. Between 5200 and 5700 cal yr BP, and after a major volcanic eruption, both assemblages were dominated by littoral aquatic macrophyte species indicators, such as Alona intermedia (type) and the Psectrocladius sordinellus group. The ratio of littoral/planktonic (L:P) assemblages was low, indicating shallow lake conditions. Between 2100 and 5200 cal yr BP, an increase of planktonic and profundal chironomid taxa, suggesting lake deeper conditions. This period was also characterized by great volcanic activity on the Caveiro Lake, resulting in increased production of cladoceran resting eggs. Between 1800 and 2100 cal yr BP, coinciding with peat formation in the lake margin, an arid period was identified, reflected by the low abundance of subfossil remains of both assemblages, and the presence of high plant macro rests in the sedimentary sequence. Between 500 and 1800 cal yr BP, large changes in the L:P ratio were recorded, including the appearance of stream indicators taxa, such as Simulium sp., Zavrelimyia sp. and Rheocriotopus fuscipes type all suggesting a period characterized by climate instability. After 500 cal yr BP to nowadays the drastic reduction of total abundance and taxon diversity on both assemblages, which coincides with the establishment of the Portuguese colonizers, reflects forest clearance in lake catchment and the introduction of exotic species ...